SPE International Symposium and Exhibition on Formation Damage Control 2010
DOI: 10.2118/127919-ms
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Data from the Barnett Shale Using Conventional Statistical and Virtual Intelligence Techniques

Abstract: A Barnett Shale water production dataset from approximately 11,000 completions was analyzed using conventional statistical techniques. Additionally a water-hydrocarbon ratio and first derivative diagnostic plot technique developed elsewhere for conventional reservoirs was extended to analyze Barnett Shale water production mechanisms. In order to determine hidden structure in well and production data, self-organizing maps and the k-means algorithm were used to identify clusters in data. A competitive learning b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Studies by others [Awoleke and Lane, 2010] and our own work have demonstrated that a few variables have greater effect than others. Horizontal/vertical orientation, obviously, and local geology are among the most important factors.…”
Section: Choosing Analogsmentioning
confidence: 45%
“…Studies by others [Awoleke and Lane, 2010] and our own work have demonstrated that a few variables have greater effect than others. Horizontal/vertical orientation, obviously, and local geology are among the most important factors.…”
Section: Choosing Analogsmentioning
confidence: 45%
“…Mohaghegh (2000) published an excellent summary of the application of neural networks in petroleum engineering. A more recent summary is also available (Awoleke 2009). Neural networks (feed-forward type) usually consist of an input layer (number of nodes in the input layer depends on the dimensionality of the data set), one or more hidden layers (number of layers/neurons is dependent on problem complexity), and one output layer (number of neurons dependent on the number of output variables).…”
Section: Water-production Sources and Mechanisms In The Barnett Shalementioning
confidence: 99%
“…ANN has achieved significant popularity in areas such as production prediction , reservoir characterization or properties prediction (An et al 1993, Goda et al 2003, Tang et al 2011, history matching (Ramgulam 2006), classification (Stundner et al 2001), proxy for prediction of recovery performance (Lechner et al 2005, Awoleke et al 2011, production operation optimization and well design (Stoisits et al 1999, Yeten et al 2002, Ayala H et al 2007). In recent years, the neural network has also been utilized to evaluate enhanced oil recovery (EOR) projects (Zerafat et al 2011, Parada et al 2012, predict heavy oil recoveries (Ahmadloo et al 2010, Popa et al 2012, and assess CO 2 sequestration process (Mohammadpoor et al 2012).…”
Section: Introductionmentioning
confidence: 99%